Prevalencia de la delincuencia juvenil en Santiago de Cali. - Sanabria , Ana María (2022)
This paper presents delinquency acts prevalence among the Colombian youth. The case studies data gathered from the National Police where the youth had been reported with delinquent acts in 2003 in Santiago de Cali. The analysis unit had 3677 young men and women, ages 10 to 17 that had a criminal record belonging to the different city areas. The average age among the group was of 15.75. The most common delinquent act was common theft, followed by drug trafficking on women and carrying illegal fire arms on men. Sixteen and seventeen year old men had the highest index of delinquency as compared to women. The results show the importance of biological and evolving variables such as age and sex in the manifestation of this behavior . As a consequence, it is very important to start with separate age and gender intervention programs that can generate a positive impact on these people for the prevention and lowering of juvenile delinquency